Human trafficking: examining the facts - Lederer, Laura (Contemporary debates, 2024)
Cover -- Half Title -- Series -- Title -- Copyright -- Epigraph -- Contents -- Illustrations -- How to Use This Book -- Acknowledgments -- 1 Numbers Never Lie? Estimating the Nature and Scope of Human Trafficking -- 2 The 3P Framework: Prevention, Prosecution, and Protection and Assistance -- 3 Survivors: Language, Image, Life -- 4 Countering Trafficking in Persons -- 5 Learning from Lived Experience: What Survivors Are Telling Us -- 6 The Long Arc of Slavery -- Index.